Isomorphic web applications : universal development with React - Gordon, Elyse Kolker (Manning Publications, 2018)
Isomorphic Web Applications teaches you to build production-quality web apps using isomorphic architecture. You'll learn to create and render views for both server and browser, optimize local storage, streamline server interactions, and handle data serialization. Designed for working developers, this book offers examples in relevant frameworks like React, Redux, Angular, Ember, and webpack. You'll also explore unique debugging and testing techniques and master specific SEO skills.